Banana stew and brew on Uganda's menu - Daniells, J.W.; Karamura, D. (Australian Banana Growers Council, 2014)
Ugandans eat more bananas than anyone else, drink banana beer and have a word for a banana variety which also means “food”. Jeff Daniells of Queensland’s Department of Agriculture, Fisheries and Forestry (QDAFF) attended an international banana workshop in Uganda. He provided this report with Deborah Karamura of Bioversity International, Uganda.